CHARACTERISTICS OF THE IMMUNE MICROENVIRONMENT OF THE NORMAL MUCOUS MEMBRANE OF THE PERITUMORAL AREA IS AN ADDITIONAL INDEPENDENT PROGNOSTIC FACTOR IN GASTRIC CANCER - N. V. Danilova; V. M. Kkomyakov; A. V. Chayka; I. A. Mikhailov; N. A. Oleynikova; P. G. Malkov (Сибирский онкологический журнал, 2021)
The aim of the study was to study and evaluate the predictive value of the immune microenvironment of gastric cancer and morphologically normal mucous membrane of the peritumoral area using an automatic morphometric analysis system on the example of CD 8+ cells.Material and Methods. Surgical samples from 130 patients with a verified diagnosis of gastric cancer were used. After immunohistochemical staining with antibodies to CD 8, a morphological assessment was performed according to the original method. We assessed the average area of CD 8+ cells in three fields of view (lens magn. ×20) using the automatic system of morphometric analysis LAS X (Leica) in the central part of the tumor and areas of morphologically normal mucous membrane of the peritumoral region directly adjacent to the tumor tissue. The results were compared with the main clinical and morphological characteristics of the tumor as well as with the overall five-year survival of patients.Results and Discussion. A high density of CD 8+ infiltration of normal mucous membrane of the peritumoral area was observed in groups T4a and T4b by the depth of invasion (n=96, p=0.0089) and was associated with the presence of emboli in the lymphatic vessels (n=96, p=0.0102) and with the more advanced stage of gastric cancer (n=96, p=0.0107). The studied cases were divided into two groups: less than 3300 square micrometers (better patient survival; n=79, p=0.01) and more than 3300 square micrometers according to the average area of CD 8+ cells in normal mucous membrane of the peritumoral area. According to multivariate survival analysis using the Cox regression model, it was found that the average area of CD 8+ cells in normal mucous membrane of the peritumoral area was a significant negative prognostic factor (RR=1.537; CI : 0.761–3.105; p<0.01) comparable in degree covariance with the stage of the tumor A similar indicator assessed in central part of the tumor was not significantly associated with patient survival (RR=0.803; CI : 0.574–1.122; p>0.05).Conclusion. The possibility of using an automatic analysis system to evaluate the immune microenvironment in gastric cancer was demonstrated for the first time. It was found that a high level of CD 8+ lymphocyte infiltration of morphologically normal mucous membrane of the peritumoral area was an independent negative prognostic factor. Therefore, we recommend the mandatory preoperative biopsy sampling from the mucous membrane of the peritumoral region for morphometric assessment of CD 8+ lymphocyte infiltration.